Influencing Factors of the Pharmacokinetic Characters on Nanopharmaceutics - Ji, Xiwei; Lu, Wei; Wu, Kehua; C. Cho, William (Pharmaceutical Nanotechnology, 2017)
Background: Nano-pharmaceutics have been actively studied for the encapsulation and targeted delivery of drugs to improve the treatment strategies for various diseases. Because of the size, nano-pharmaceutics show some special characteristics of pharmacokinetics (PK). There are quite a number of studies focusing on the efficacy and toxicity of nano-pharmaceutics. However, only few of them investigated PK. Method: Literature search was conducted to summarize recent studies on PK of nano-pharmaceutics. Result: Both the efficacy and toxicity of nano-pharmaceutics are associated with their absorption, distribution, metabolism and elimination (ADME). Absorption mainly affects bioavailability, while distribution gears with target delivery. Both absorption and distribution play important roles in the efficacy of nano-pharmaceutics. Metabolism and elimination are the major influencing factors for the toxicity of nano-pharmaceutics. PK models and physiologically-based PK models can be powerful tools to analyze and predict the in vivo behavior of nano-pharmaceutics based on experimental data. Conclusion: Further research will be needed to investigate the underlying mechanism between the ADME processes of nano-pharmaceutics and their efficacy and toxicity.
Keywords: ADME